Price Impacts of Non-Adoption of the Euro for Small European Countries - Anderson, Harald (IMF Working Papers; Working Paper ;, 2006)
Debates surrounding the adoption of a common currency have focused on its benefits weighed against the long-term costs of losing monetary independence. These debates have assumed that the penalty for not adopting a common currency is the maintenance of the status quo. This paper uses the Sjaastad model to analyze the price-making power of major currencies with regard to the prices of traded goods in small countries that have not adopted the euro and uses the Bayoumi-Eichengreen OCA index methodology to shed further light on changes in Europe. The empirical evidence suggests that small countries that have not adopted the euro have increasingly seen a change in the determinants of their traded goods prices. This seems to contrast with the experience of small countries that adopted the euro. The results need to be interpreted carefully, given the short time series.